KONSTRUKSI IDENTITAS POSTMODERN DALAM IKLAN LA LIGHT VERSI âDONT QUITâ - Surahman, Sigit (KEMADHA, 2012)
n the postmodern era and the economic, political , social and cultural erratic in Indonesia today , present the medium of television led to a new phenomenon in the world of audio visual advertising . Cigarette advertising LA LIGHT version of " Do not Quit " which brings various questions . Serving ads presented , does not show any relationship between the messages being delivered to the marketed product .Display advertising LA LIGHT version of " Do not Quit" , in this paper cigarette advertising LA LIGHT version of " Do not Quit" , examined the postmodern linguistic approach , namely semiotic theory , a theory derived from the language theory. Between signifier ( form ) and signified ( meaning ) in the display advertising LA LIGHT version of " Do not Quit " it seems there is no ideological and well-established relationship , but it appears that perceptions in packing quite ironic in its entirety . Serving advertisements LA LIGHT version of " Do not Quit " also seems to combine aspects of life that evolved in that time , so the text , the language , both audio and visual ( are works of post - modern ) not only produce a single meaning , but a multidimensional space in which it is mixed diffuse , interact , and contrary to various problems . These ads indicate the use of the postmodern aesthetic language that is visual semiotics linguistics and semiotics .